Glyphosate como regulador de crescimento em arroz de terras altas - Gitti, Douglas de Castilho [UNESP] (2011)
The lodging of some rice cultivars at harvest time can lead to significant losses in yield, and the inappropriate water and nitrogen management, under high-tech conditions, can aggravate the problem. The use of vegetal regulators is an alternative to reduce lodging, however, information on this topic are rare. The study aimed to evaluate the application of glyphosate sub doses (26 g ha -1, 52 g ha -1, 78 g ha -1, 104 g ha -1, 130 g ha -1, 156 g ha -1, and 182 g ha -1) on agronomical traits, development, and yield of upland rice crops irrigated by aspersion, during the floral differentiation period. The experiment was carried out in Selvíria, Mato Grosso do Sul State, Brazil, through the agricultural years of 2008/2009 and 2009/2010. The increase of glyphosate sub doses, at the floral differentiation period of the Primavera cultivar, reduced the plants height, panicle size, and, consequently, yield. Sub doses higher than or equal to 78 g ha -1 eliminated the plants lodging process.